Hue of aspiration reflected the nature of poison and cause of death: A case report of copper sulphate ingestion - Malik, Yogender; Khanna, Kunal; Vasisht , Yogesh (Journal of Indian Academy of Forensic Medicine, 2021)
Most of the times, the cause of death in suspected poisoning cases is given only after receipt of chemical analysis report. In inquest  papers it is usually mentioned as unknown poisoning as the suspected cause of death. Here we are presenting a case brought dead in  casualty of PGIMS, Rohtak with a history of consumption of some unknown poisonous substance at home. During post-mortem  examination bluish coloured granular semi-liquid aspirated material was observed in the esophagus and trachea reaching up to the  bronchioles which indicated not only the immediate cause of death as aspiration of gastric contents, but, also the nature of poison i.e.  Copper Sulphate which is believed to be a rare poison nowadays. The detail of this case with photographs has been discussed.
Keywords: Copper sulphate; Poisoning; Aspiration